The Research Utility of the National Violent Death Reporting System for Understanding Homicide Trends - Rogers, Ethan M. (Journal of contemporary criminal justice, 2024)
Homicide trend research has relied heavily on the same two data systems for decades. The current article highlights the research utility of a newer database—the National Violent Death Reporting System (NVDRS)—for examining the contours of homicide change. First, we describe the history, design, and availability of the NVDRS, and review past homicide and longitudinal studies using these data. Second, we discuss two features of the data system that researchers should consider when conducting homicide trend analyses: (a) data availability and representativeness and (b) data completeness. Third, we demonstrate a strong degree of correspondence between NVDRS homicide victimization trends and trends from other data systems. Fourth, we illustrate the ways in which the NVDRS can enrich our understanding of homicide trends by examining how homicide characteristics changed during the two recent homicide spikes from 2014 to 2016 and 2019 to 2020.